Application of Expert Systems for Financial Analysis - Stungurienė, Stanislava (Ekonomika, 1999)
This paper discusses the main principles of searching new computeraided financial analysis technologies. Currency risk management is the very core for such study. The subject is the issue of how to combine in a knowlidge-based way the currency exposure of an investor or of a company in view of a set of N assets and liabilities in two currencies. The model of currency risk management procedure as an illustration is used with that end in view to explain the searching new techniques for solving financial analysis problems. The Artificial Inteligence theory is a means for founding progressive computeraided systems in domain of economics and financial. The main principles of Artificial Inteligence applicability are proposed.